Degree of intrapartum fever and associated factors: Three group analysis of no fever, borderline and overt fever. Issue 3 (12th January 2021) - Kim, Seo‐Yeon; Hong, Sir‐Yeon; Kwon, Do Youn; Park, Hyea; Choi, Suk‐Joo; Oh, Soo‐Young; Kim, Jung‐Sun; Choi, Duck Hwan; Roh, Cheong‐Rae
Abstract: Aim: Previous studies analyzing intrapartum fever by dichotomization of fever just above 38.0°C or not may lead to overlook clinical significance of borderline fever. We aimed to investigate the maternal baseline and intrapartum characteristics, neonatal outcomes, and inflammatory placental pathology in relation to the degree of intrapartum fever by three group analysis. Methods: We performed a retrospective analysis of consecutive singleton deliveries between 37 0/7 to 41 0/7 weeks divided into three groups based on the peak body temperature during labor: No fever (< 37.5°C), borderline fever (≥ 37.5°C and < 38.0°C), and overt fever (≥ 38.0°C). Maternal and intrapartum characteristics, neonatal outcomes, and inflammatory placental pathology were compared by trend analysis, intergroup difference analysis, and multivariable analysis. Results: The degree of intrapartum fever was significantly associated with younger maternal age, nulliparity, longer duration of rupture of membrane, and epidural analgesia ( p < 0.001). And the incidence of neonatal proven sepsis and mortality were not significantly different among the groups. The degree of intrapartum fever was associated with the stage of acute chorioamnionitis and funisitis ( p < 0.001). Multivariate analysis revealed that the association with epidural analgesia was stronger in borderline fever than overt fever (adjusted odds ratio [95% confidence interval], borderline fever = 18.487 [11.447–29.857]; overt fever = 11.068 [4.874–25.133]) after controlling for maternal age, parity, induction or augmentation, duration of ROM, birth weight, and meconium staining. Conclusion: Our data support that both epidural analgesia and inflammation of the placenta may contribute to the development of intrapartum fever at term.